KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP PEMBANGUNAN LABORATORIUM UNP - Mulia, Muhammad Jaka; Tamsin, Andria Catri (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACT Research purposes. First, describe students' reading comprehension skills. Second, describe the skills of writing Description text. Third, describe the correlation between reading comprehension skills and text writing skills Description of Grade VII students of the UNP Laboratory Development Middle School. This type of quantitative research is a correlational method. The study design was correlational two variables. The research population of VII grade students of SMP UNP Laboratory Development registered in the academic year 2019/2020 total 142 students in five classes. The sample in the study was 37 people. Samples were taken by simple 25% random technique using proportional random sampling technique. The research instruments were performance tests, description writing text tests and objective reading comprehension skills tests.Â Conclusion. First, students' reading comprehension skills are in good qualifications (78.98). Second, the students' written text description skills are in good qualifications (83,12). Third, reading comprehension skills correlate with text writing skills Description of VII graders of SMP UNP Laboratory Development with degrees of freedom n-2 at 95% confidence level. T value is greater than t table that is 2.637> 1.68, thus H0 is rejected and H1 is accepted because the test results prove that t count is greater than t table. the conclusion "There is a correlation between reading comprehension skills and writing skills text. Description of Grade VII students of SMP UNP Laboratory Development" was accepted. This means that the better the students 'reading comprehension skills, the better the students' writing text description skills.Â Kata kunci: Keterampilan Membaca Pemahaman, Keterampilan Menulis, Teks Deskripsi, Korelasi